2023
DOI: 10.1136/bmj-2022-072133
|View full text |Cite
|
Sign up to set email alerts
|

Medial retropharyngeal nodal region sparing radiotherapy versus standard radiotherapy in patients with nasopharyngeal carcinoma: open label, non-inferiority, multicentre, randomised, phase 3 trial

Abstract: Objectives To address whether sparing the medial retropharyngeal lymph node (MRLN) region from elective irradiation volume provides non-inferior local relapse-free survival versus standard radiotherapy in patients with nasopharyngeal carcinoma. Design Open-label, non-inferiority, multicentre, randomised, phase 3 trial. Setting Three Chinese hospitals between 20 November 2017 and 3 December 2018. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 33 publications
3
16
0
Order By: Relevance
“…Much less effort has been put into the artistry of oncology, such as refining the delineation of target volumes in radiation planning, albeit a significantly less cost-effective and labor-intensive approach [3][4][5][6]. Recently, Mao et al [7], in a multicenter randomized phase III trial, demonstrated how sparing of the medial retropharyngeal nodal group alone in radiation planninga process that solely relies on human intelligence without any additional human effort or technological resources -results in 39% reduction in ≥ grade one clinician-rated acute dysphagia and 24% reduction in ≥ grade one weight loss. In addition, there was a significant improvement in patient-reported quality-of-life outcomes at 3 years, such as global health status, role-social function and swallowing function.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Much less effort has been put into the artistry of oncology, such as refining the delineation of target volumes in radiation planning, albeit a significantly less cost-effective and labor-intensive approach [3][4][5][6]. Recently, Mao et al [7], in a multicenter randomized phase III trial, demonstrated how sparing of the medial retropharyngeal nodal group alone in radiation planninga process that solely relies on human intelligence without any additional human effort or technological resources -results in 39% reduction in ≥ grade one clinician-rated acute dysphagia and 24% reduction in ≥ grade one weight loss. In addition, there was a significant improvement in patient-reported quality-of-life outcomes at 3 years, such as global health status, role-social function and swallowing function.…”
mentioning
confidence: 99%
“…In a study of 3,100 newly diagnosed NPC, using contemporary MRI techniques, medial PRLN involvement was only identified in 0.2% of the patients, and they were all located at the level of the second or third cervical vertebra [8]. The group by Mao et al [7], by leveraging and transferring the knowledge of lymphatic development and pattern of tumor spread -human intelligence -into clinical treatment planning and toxicity reduction.…”
mentioning
confidence: 99%
See 3 more Smart Citations